2004
DOI: 10.7326/0003-4819-141-12-200412210-00007
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture versus Placebo for the Treatment of Chronic Mechanical Neck Pain

Abstract: Acupuncture reduced neck pain and produced a statistically, but not clinically, significant effect compared with placebo. The beneficial effects of acupuncture for pain may be due to both nonspecific and specific effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 31 publications
3
110
1
1
Order By: Relevance
“…In 1 of these RCTs (44), the sham involved patch electrodes that used mock electrical stimulation and were attached to the same 4 knee points used in the true acupuncture group. Because no needles were used, patients randomly assigned to the sham group probably did not believe that they were receiving traditional acupuncture, although they may have believed that they were receiving a credible treatment (54). In the other RCT that found large, clinically relevant benefits of acupuncture (46), the sham needles did not penetrate the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 of these RCTs (44), the sham involved patch electrodes that used mock electrical stimulation and were attached to the same 4 knee points used in the true acupuncture group. Because no needles were used, patients randomly assigned to the sham group probably did not believe that they were receiving traditional acupuncture, although they may have believed that they were receiving a credible treatment (54). In the other RCT that found large, clinically relevant benefits of acupuncture (46), the sham needles did not penetrate the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies have shown that acupuncture has not been more effective than placebo in reducing chronic neck pain (20)(21)(22). It seems that different results obtained from multiple studies can be attributed to the problems with studying the pain itself, which is a personal emotional impression, and examining its reduction in the studies can give different results in different cultures.…”
Section: Discussionmentioning
confidence: 90%
“…This is exemplified by the act of acupuncture. Simulating the manner in which an acupuncture needle enters the person's body, without actually piercing the skin is one problematic aspect (Ernst, 1994;Ryan, 1999;Vincent & Lewith 1995;White, Lewith, Prescott, & Conway, 2004). A credible placebo must mimic the acupuncture needle insertion, yet not enter or heavily pressure the skin, because this could create the acupuncture effect.…”
Section: Research Into Acupuncturementioning
confidence: 99%